Preparing adult educators for racial justice. Issue 170 (12th September 2021) - Isaac‐Savage, E. Paulette; Merriweather, Lisa R.
Abstract: Adult educators are often seen as proponents of social justice but what does it really mean to be an advocate for racial justice in and outside the classroom? Draconian policies implemented by the Trump administration have placed additional hardships on Americans. The increasing attacks on education have clear ramifications for adults in formal and informal contexts. In this article, the authors will explore how adult educators can become not only allies for social justice but also advocates and accomplices for racial justice through curriculum, instruction, and altered perceptions. Social justice is a broad term capturing all aspects of injustice. Racial justice focuses squarely on injustices due to race and racism.